Bootstrapping of a rule based English-Bangla machine translation system using work done for a sister language - Tahin, E.M. Yeaseenur Rahman (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2010.